Environmental consequences of dread behavior: A note on 2005 London bombings. (March 2019) - Percoco, Marco
Abstract: The aim of this paper is to identify the environmental impact induced by behavioral responses to terrorist attacks occurred in London on July 7th, 2005. By relying on the "dread hypothesis" and on the evidence of an increase in private transport subsequent attacks, we have estimated econometric models of pollution concentration. Our results point at a substantial environmental impact in terms of PM10 and NO2, possibly driven by an increase in the perception of higher safety of private transport with respect to public transit. Results are robust to several robustness checks, including nonlinear time trends and heterogeneity across types of monitoring stations.